Packed red cell transfusions in preterm neonates: a retrospective study - Ivena Clairine Sulistio; Delicia Rudy; Putu Siska Suryaningsih; I Wayan Bikin Suryawan (Medical Faculty of Brawijaya University, Indonesia, 2025)
Introduction: Preterm neonates are highly vulnerable to anemia. Packed red cell (PRC) transfusions are often necessary but must be carefully considered due to associated risks. This study aims to assess the characteristics of preterm infants who received PRC transfusions to guide safer and effective transfusion practices. Methods: This study was conducted using a retrospective descriptive approach. It included preterm neonates who received PRC transfusions, as documented in the medical records from July 2022 to March 2025. Patient characteristics, hemoglobin level, transfusion profile, and comorbidities in preterm neonates receiving PRC transfusions were evaluated. Results: The sample consisted of 52 neonates, 37 boys, and 15 girls. The gestational age of infants was mainly between 28 and <32 weeks (64,5%). Most neonates were very low birth weight, which is 53,8%. The mode of delivery was relatively similar between spontaneously and cesarean section. The average length of hospital stay was 35.27 ± 16.62 days. The initial hemoglobin level of preterm infants receiving PRC transfusions averaged 10.88 ± 1.33 g/dL. The first transfusion was typically administered at 18.10 ± 9.69 days of life. Notably, most infants (59.6%) required three or fewer transfusions. The most common comorbidity among preterm infants receiving PRC transfusions was respiratory distress syndrome (RDS) at 78.8%, followed by neonatal jaundice (53.8%) and asphyxia (40.4%). Most RDS cases (69.2%) were caused by hyaline membrane disease (HMD). Conclusion: Preterm neonates receiving PRC transfusions had a high-risk profile, underscoring the importance of individualized transfusion thresholds and close post-transfusion monitoring to improve clinical outcomes.